Letter from the editor - Carlos Alberto Vargas Jiménez (Earth Sciences Research Journal)
It's time to present our second volume of 2017. The result of a great effort to put into your hands some works of the best quality. With this selection of articles, an invitation to the Colombian Geology Congress.